#METOO in the corporate world : power, privilege, and the path forward - Hewlett, Sylvia Ann, 1946- (Harper Business, an imprint of HarperCollinsPublishers, 2020)
While the #MeToo movement has exposed the enormous harm done by sexual misconduct in the workplace, the movement<U+2019>s full promise has not been fulfilled, Sylvia Ann Hewlett argues. Showcasing new data on the incidence of sexual harassment and assault at work, she reveals how the movement has focused almost exclusively on white women and failed to support other vulnerable groups who are also targets of abuse. Black men, gay men and women, and Latinas experience particularly high rates of sexual harassment and assault.In addition to exploring the movement<U+2019>s limitations, Hewlett examines the collateral damage inflicted by #MeToo. She looks at hits to the bottom line (lawsuits and settlements, tarnished brands, and stock devaluations) and hits to the talent pipeline. In particular she shows how male leaders, fearful of gossip and legal action, are increasingly skittish about sponsoring young women, no matter how high performing they are. This makes it much more likely that women will stall out mid-career and will deprive companies of diversity in the C-Suite and “gender smarts” around decision-making tables. Digging deep into examples that range from Fox News, Nike, and Google to CBS, Michigan State University, and the Catholic Church, Hewlett lays bare the financial losses associated with sexual misconduct scandals. No wonder corporate chief risk officers newly have #MeToo in their line of sight! A third of this book is devoted to solutions and Hewlett offers a three-pronged strategy, combining legal remedies with individual and corporate action steps that can be used to protect employees and businesses they work for. Drawing from companies as different as IBM and IPG she discusses “experiments at the edge” as well as more evolved initiatives that can help any corporation create a more equitable and safer environment.